Diallel analysis of some grain yield traits in wheat - Nagar, Satnam Singh; Kumar, Pradeep; Vishwakarma, S R; Gupta, Vikas (Journal of Cereal Research, 2018)
Genetic analysis was conducted for grain yield and its component traitsin a set of 13 bread wheat genotypes following a diallel (excluding reciprocals) mating design. The analysis of variance revealed highly significant differences in mean squares due to both general combining ability (GCA) and specific combining ability (SCA) for all the eleven traits in both F1 and F2 generations. This indicated the involvement of both additive and non-additive gene action governing inheritance of traits. The σ2s was higher than σ2g and the ratio of σ2g/σ2s was less than unity (1.00) for all traits, suggesting the importance of non-additive gene action in both F1 and F2 generation. The parental genotypes NW 1014, PBW 343, PBW 502, DBW 14 and RAJ 3765 were found to be goodcombiners for multiple traits along with grain yield in both F1 and F2 generations. The seven crosses PBW 343 / K 8962, UP 2490 / CBW 38,PBW 343 / HI 1563, HP 1744 / UP 2425, HP 1744 / CBW 38, DBW 14 / CBW 38 and RAJ 3765 / UP 2490 were found to be good combiners for grain yield and its contributing multiple traits in both F1 and F2 generations and these crosses may be utilized in the development of high yielding progenies in bread wheat. Doi.org/10.25174/2249-4065/2018/77261